Integrating Social Capital and Ethnopedagogy in Social Studies: Fostering Cultural Identity and Community Resilience in Indonesia - Mutiani; Raihanah Sari; Sovia Husni Rahmia; Jumriani; Rusli; Nola Fibriyani Bte Salman (IAIN Madura, 2026)
Integrating the concept of social capital is ideal for developing social studies materials. This article aims to explore the synergy between the concept of social capital in practice and an ethnopedagogical approach that prioritizes local wisdom in social studies education in Indonesia. The method used in compiling this article is a literature review with the application of a SWOT analysis. The SWOT analysis yields strategic insights for the development of both approaches. The findings indicate that integrating ethnopedagogy into social studies can strengthen interpersonal relationships, increase community awareness, and revitalize cultural identity amidst globalization. Developing social capital through collaborative learning has been shown to foster critical thinking, empathy, and active participation in citizenship. This study proposes a conceptual model that aligns the dimensions of social capital; bonds, connections, and relationships—with ethnopedagogical strategies to achieve culturally responsive social studies learning. However, challenges such as cultural homogenization, limited teacher capacity, and symbolic cultural representations need to be addressed through policy support, professional development, and curriculum reform that respects indigenous epistemologies. Integrating these two approaches offers a transformative pathway to developing culturally grounded, socially connected, and democratically minded learners.